2012
DOI: 10.1103/physreve.85.031902
|View full text |Cite
|
Sign up to set email alerts
|

Membrane heterogeneity: Manifestation of a curvature-induced microemulsion

Abstract: To explain the appearance of heterogeneities in the plasma membrane, I propose a hypothesis which begins with the observation that fluctuations in the membrane curvature are coupled to the difference between compositions in one leaf and the other. Because of this coupling, the most easily excited fluctuations can occur at non-zero wavenumbers. When the coupling is sufficiently strong, it is well-known that it leads to microphase separation and modulated phases. I note that when the coupling is less strong, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
150
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(163 citation statements)
references
References 34 publications
10
150
3
Order By: Relevance
“…These raft-like domains grow several micrometers in size in giant unilamellar vesicles (GUVs) (7), while their mobility is preserved, whereas lipid domains in supported lipid bilayers are smaller but are largely immobile and do not form energy-minimized round shapes (10). Explanations for the size difference of lipid domains in native plasma membranes and model membranes range from the system's vicinity to a critical point (9), where density fluctuations prevail, over compositions with lipids having one saturated and one unsaturated fatty acid tail (11), coupling between composition and local membrane deformation (12)(13)(14), and the presence of the cortical cytoskeleton (15). It has been shown that attaching an artificial cytoskeleton made of actin or a tubulin homolog alters the shape and position of the ordered domains (16,17).…”
mentioning
confidence: 99%
“…These raft-like domains grow several micrometers in size in giant unilamellar vesicles (GUVs) (7), while their mobility is preserved, whereas lipid domains in supported lipid bilayers are smaller but are largely immobile and do not form energy-minimized round shapes (10). Explanations for the size difference of lipid domains in native plasma membranes and model membranes range from the system's vicinity to a critical point (9), where density fluctuations prevail, over compositions with lipids having one saturated and one unsaturated fatty acid tail (11), coupling between composition and local membrane deformation (12)(13)(14), and the presence of the cortical cytoskeleton (15). It has been shown that attaching an artificial cytoskeleton made of actin or a tubulin homolog alters the shape and position of the ordered domains (16,17).…”
mentioning
confidence: 99%
“…We simulate a system of size L = 400 with lattice spacing a = 2 nm. For the presented results, we use a typical value βκ = 70 for the bending rigidity [27,30]. At room temperature, T = 300 K, this corresponds to κ = 2.9 × 10 − 19 Nm, which is close to the value used in Ref.…”
Section: Membrane "Sandwiched" Between a Solid Substrate And An Actinmentioning
confidence: 81%
“…The pinning sites along the actin fibers locally push the membrane down, leading to non-zero average curvature below the fibers. Consider now a lipid mixture, with one of the lipid species preferring regions of, say, positive curvature (the coupling between membrane composition and curvature is an established fact [30][31][32][33][34][35]). In the upper membrane leaflet, these lipids would then preferentially collect underneath the actin fibers, since there the curvature has the correct sign.…”
Section: Membrane "Sandwiched" Between a Solid Substrate And An Actinmentioning
confidence: 99%
“…Equilibrium microphase separation in two-component lipid membranes was found in two-leaflet models with different lipid composition in each leaflet [13][14][15][16]. In these models, coupling between the local membrane curvature and the difference of local lipid compositions in two layers could give rise to an instability at finite wave numbers.…”
mentioning
confidence: 96%
“…In nonequilibrium systems, an analog of the microphase separation can be observed when energetically activated reactions between two components are included [5,6]. The nonequilibrium scenario has inspired a variety of proposals in the context of the cell membrane [7][8][9][10][11][12].Equilibrium microphase separation in two-component lipid membranes was found in two-leaflet models with different lipid composition in each leaflet [13][14][15][16]. In these models, coupling between the local membrane curvature and the difference of local lipid compositions in two layers could give rise to an instability at finite wave numbers.…”
mentioning
confidence: 99%